The growth of high tech academic spin-offs and the role of the parent organization: the case study of University of Turin - Candelo, Elena; Sorrentino, Mario; Cantino, Valter (Piccola Impresa / Small Business, 2016)
The importance of academic spin-offs as a possible driver of economic and social development is now widely recognized, and their University of origin is a significant variable. The paper analyses the role of specific resources provided by university of origin in the spin-off growth process: technology transfer office, university brand and incubator presence. The research method is qualitative. It’s based on the analysis of four high-tech academic spin-offs created in University of Turin and already on the market. In particular investigation process analyzes the role of the three cited resources in overcoming obstacles faced by the spin offs in their various development phases and identifies key resources to overcome them. Therefore the article provides important managerial implications on the role that the University of origin should have in the academic spin-offs growth.